The Jurisdiction Of The Federal Supreme Court Of Iraq In Deciding On The Validity Of The Membership Of The Iraqi Parliament Council - Abdulkadhim Oufi, Mohammad; Abdalhosain Balasem, Hosam (Opción, 2019)
After the end of the parliamentary elections for the Parliament elections, several problems arise that affect the legal status of the elected member, and the matter may reach the termination of the membership of one of the deputies and his exclusion, in addition to this exclusion may result in his replacement by another candidate from the same political entity or from the same electoral district or According to the votes obtained by each candidate, this occurs as a result of the violation of one or some of the conditions required by the consti- tution or laws related to the candidate for membership in the Parliament, but to ensure the validity and seriousness of the decision, not only on the member, but the effects of this extend to include the Parliament, because excluding The MP leads to a decrease in the number of parliamentary seats in the Council, as well as the lack of the number of constituency seats or political entity that has followed him this member.